Cerebral hemodynamic response to upright position in acute ischemic stroke - Carvalho, Lilian B.; Kaffenberger, Tina; Chambers, Brian; Borschmann, Karen; Levi, Christopher; Churilov, Leonid; Thijs, Vincent; Bernhardt, Julie (Frontiers in Neurology, 2024)
Introduction Concerns exist that a potential mechanism for harm from upright activity (sitting, standing, and walking) early after an acute ischaemic stroke could be the reduction of cerebral perfusion during this critical phase. We aimed to estimate the effects of upright positions (sitting and standing) on cerebral hemodynamics within 48 h and later, 3–7 days post-stroke, in patients with strokes with and without occlusive disease and in controls. Methods We investigated MCAv using transcranial Doppler in 0° head position, then at 30°, 70°, 90° sitting, and 90° standing, at <48 h post-stroke, and later at 3–7 days post-stroke. Mixed-effect linear regression modeling was used to estimate differences in MCAv between the 0° and other positions and to compare MCAv changes across groups. Results A total of 42 stroke participants (anterior and posterior circulation) (13 with occlusive disease, 29 without) and 22 controls were recruited. Affected hemisphere MCAv decreased in strokes with occlusive disease (<48 h post-stroke): from 0° to 90° sitting (−9.9 cm/s, 95% CI[−16.4, −3.4]) and from 0° to 90° standing (−7.1 cm/s, 95%CI[−14.3, −0.01]). Affected hemisphere MCAv also decreased in strokes without occlusive disease: from 0° to 90° sitting (−3.3 cm/s, 95%CI[−5.6, −1.1]) and from 0° to 90° standing (−3.6 cm/s, 95%CI [−5.9, −1.3]) (p-value interaction stroke with vs. without occlusive disease = 0.07). A decrease in MCAv when upright was also observed in controls: from 0° to 90° sitting (−3.8 cm/s, 95%CI[−6.0, −1.63]) and from 0° to 90° standing (−3 cm/s, 95%CI[−5.2, −0.81]) (p-value interaction stroke vs. controls = 0.85). Subgroup analysis of anterior circulation stroke showed similar patterns of change in MCAv in the affected hemisphere, with a significant interaction between those with occlusive disease (n = 11) and those without (n = 26) (p = 0.02). Changes in MCAv from 0° to upright at <48 h post-stroke were similar to 3–7 days. No association between changes in MCAv at <48 h and the 30-day modified Rankin Scale was found. Discussion Moving to more upright positions <2 days post-stroke does reduce MCAv in the affected hemisphere; however, these changes were not significantly different for stroke participants (anterior and posterior circulation) with and without occlusive disease, nor for controls. The decrease in MCAv in anterior circulation stroke with occlusive disease significantly differed from without occlusive disease. However, the sample size was small, and more research is warranted to confirm these findings.